Automasi Administrasi Digital dalam Peningkatan Pelayanan Nagari Ranah Pasisie - Lita Sari Muchlis; Kasma Putra, Fitra; Rahmi, Lidya; Iswandi; Adriyendi; Afif, Zihnil; Sayuti, Alwi Farid (Universitas Putra Indonesia YPTK Padang, 2024)
Information technology has developed into a necessity in various aspects, including the government. Proper use of technology will increase the efficiency and effectiveness of organizations, especially in public services. Currently, the Nagari Ranah Pasisie government is facing challenges in providing services to the community, especially in managing village data. This service research aims to assist village officials in using Microsoft Excel within digital administration systems. Microsoft Excel can help village administrators manage, store, and administer data. Participatory action research (PAR) divides this service research method into three stages: mapping, which includes the precondition stage and needs assessment through direct communication and focus group discussion (FGD); implementation, which includes the program planning and training implementation stages; and monitoring, which includes the evaluation and reflection stages. Village officials who are training participants receive questionnaires as part of the evaluation process. The questionnaire was calculated and analyzed using a Likert scale and scale range equations. The results of the questionnaire showed that the village officials gave a positive response to the implementation of service activities. However, there were still notes, such as the duration of training needing to be increased. The training will enable village officials to provide data management and administrative services more effectively and efficiently